BIM in principle and in practice - Barnes, Peter Thomas; Davies, Nigel (ICE Publishing, 2014)
Covering the principles behind BIM, its current use in practice and how it may develop in the future, BIM In Principle and In Practice provides construction professionals with an overview of this emerging field to enable informed discussion with clients and colleagues. This new book will enable you to answer the questions: what is BIM?; how can I apply it in practice?; and how could it develop in the future at both practical and legal levels'. Relevant to all companies and projects, whatever their size and geographical market, the up-to-date advice and illustrative case studies within this book forms the ultimate practical guide to current practice and a valuable vision for the future.
Includes index.
Keywords: Building information modeling.; Building -- Computer simulation.; elektronické knihy; electronic books